Investigating the thermal properties of n-hexacosane/graphene composite: A highly stable nanocomposite material for energy storage application. (1st March 2023) - Khanna, Sakshum; Paneliya, Sagar; Prajapati, Parth; Chaudhari, Rakesh; Vora, Jay; Jouhara, Hussam
Highlights: Fabrication of stable n -hexacosane impregnated graphene nanosheet (GrPCM) nanocomposite using modified chemical process. Exudation test was performed for leakage of PCM. Investigating the effect of thermal cycling on GrPCM composite. Enhanced thermal conductivity ∼12.63 W/m K of GrPCM was observed as compared to pure PCM. Abstract: The present work demonstrates a modified chemical synthesis route (chemical, hydrothermal methods, and sonication) for fabricating n -hexacosane-impregnated graphene nanosheets (GrPCM) nanocomposite, exhibiting enhanced thermal stability in energy storage. The exfoliation of the graphene sheet during the hydrothermal and sonication process increases the surface area that can absorb n -hexacosane, improving the impregnation and interaction between them. Scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy were used to examine the morphological and structural characteristics of the GrPCM nanocomposite. The findings demonstrate the loading of n -hexacoreferesane PCM materials into porous nanosheet structures without any chemical reactions. Thermo-gravimetric analysis (TGA), differential scanning calorimetry (DSC), and infrared thermography (IR) were used to measure the latent heat, mass loss, thermal conductivity, and stability of as-synthesized GrPCM nanocomposites. The melting and solidification of GrPCM nanocomposite were observed at 57.11 ◦ C with a latent heat of 154.61 J/g and 49.28 ◦ C with a latent heat of 147.58 J/g, respectively. The GrPCM nanocomposites showed a thermal conductivity of 12.63 W/m K, which is enhanced compared to that of pure PCM materials of around 0.26 W/m K. Thermal performance measurements using infrared thermography revealed a significant increase in the nanocomposite's thermal conductivity over n -hexacosane, which was attributed to the reduced graphene nanosheet. Further, to study the heat transfer between fluid and different nanocomposites, the GrPCM nanocomposites were investigated inside a thermal storage tank. The experimental results were found in agreement with the COMSOL simulation and confirms GrPCM3 to be an excellent composite material for efficient heat transfer processes.